2022
DOI: 10.1177/00302228221095710
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Death Anxiety and Related Factors Among Nurses

Abstract: This systematic review aimed to summarize the evidence regarding death anxiety (DA) and related factors among nurses. Scopus, PubMed, Web of Science, Iranmedex, and Scientific Information Database (SID) databases were extensively searched using purpose-related keywords from the earliest to October 5, 2021. A total of 6819 nurses were included in 31 studies. The DA of nurses based on the Templer’s Death Anxiety Scale was moderate. Factors such as personal anxiety, frequency and severity of job stress, burnout, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Death is a biological phenomenon and inevitable, which thinking about it can have adverse psychological consequences in nurses. One of these effects is anxiety and stress caused by death which is called death anxiety (DA) [1,2]. DA is a complex concept that includes aspects such as the denial of death, fear of one's own death and the death of others, avoidance of discussions about death, and a hesitancy to engage with individuals who are nearing the end of life [3].…”
Section: │ Introductionmentioning
confidence: 99%
“…Death is a biological phenomenon and inevitable, which thinking about it can have adverse psychological consequences in nurses. One of these effects is anxiety and stress caused by death which is called death anxiety (DA) [1,2]. DA is a complex concept that includes aspects such as the denial of death, fear of one's own death and the death of others, avoidance of discussions about death, and a hesitancy to engage with individuals who are nearing the end of life [3].…”
Section: │ Introductionmentioning
confidence: 99%
“…In intensive care units, nurses are exposed to the risk of psychophysical and emotional distress (9,10) in the face of numerous hardships, including patient death and its consequences. Research suggests that caring for terminally-ill patients is associated with death anxiety in nurses (11)(12)(13). Dadgari et al reported moderate death anxiety in 36% and severe death anxiety in 39% of ICU nurses (14).…”
mentioning
confidence: 99%